Soil properties and grape yield affected by rock biofertilisers with earthworm compound - Pereira-Stamford,N (Chilean Society of Soil Science / Sociedad Chilena de la Ciencia del Suelo, 2011)
Grapes are an important crop in several countries, including Brazil. This study was conducted to evaluate the potential of PK rock biofertilisers on grapes (Vitis vinif-era) grown in the San Francisco Valley of the Brazilian semi-arid region. Three sources of PK fertilisers, PK soluble fertilisers, PK rock biofertilisers, and powdered PK rocks, which were all mixed with earthworm compound, and a control treatment consisting only of earthworm compound were tested at three rates. The soil pH, available P and K, exchangeable Ca+2 and Mg+2, soluble S-SO4-2, total Fe and organic carbon were analysed, and the grape yield was evaluated. The soil pH was affected by the fertilisation treatments and was reduced by the application of PK biofertiliser. The available P and K, soluble S-SO4-2, exchangeable Ca and Mg, total Fe and organic carbon in the soil increased with the application of the PK biofertilisers. The soluble fertiliser had a significant effect (p=0.01) on the recommended rate of the grape yield, but no significant difference was observed between the PK soluble fertiliser and biofertiliser at 150% of the recommended rate. Rock biofertilisers may be used as a source of P, K, S-SO4-2 and Fe for grape production in soil with low available P and K, especially if applied at a 150% recommended rate.